Exosomes derived from epidermal growth factor-like domain protein 6-preconditioned mesenchymal stem cells for diabetic wound healing - Chen Gong; Chengde Xia; Linbo Liu (Regenerative Therapy)
Diabetic wounds are difficult to repair effectively in the clinic. Tissue engineering based on mesenchymal stem cells (MSCs) showed great therapeutic potential in wound healing. MSCs-derived exosome could reproduce the effect of MSCs by transferring the bioactive substance to the recipient cells. The biological function of exosomes was determined by the state of the derived MSCs. In this study, we cultured hUC-MSCs with EGFL6 and isolated EGFL6-preconditioned exosomes (EGF-Exos), and then investigated the effect of EGF-Exos on wound healing. The results revealed that EGF-Exos promoted the proliferation and migration of HUVECs, had the anti-inflammtory function and improved angiogenesis. Moreover, we fabricated Gelama hydrogel to load EGF-Exos to repair diabetic wounds. In vivo results showed that EGF-Exos contributed to the repair of diabetic wound and provided valuable data for understanding the role of EGF-Exos in diabetic wound healing.